River Tamarind (Leucaena leucocephala) Pea Pods as Carbon Electrode for Microbial Fuel Cell - Belen, Nicole Angelika C. (Animo Repository, 2023)
With global energy security as the ultimate goal, efforts have been made in a number of countries to produce energy from a variety of sources. There is an urgent need to seek alternative methods of generating energy. Thus, the researchers proposed a study that aims to produce activated carbon from River Tamarind (Leucaena leucocephala) pods that may be utilized as an electrode in a microbial fuel cell. The main goal of this study was to compare the output voltage produced by an electrode made from river tamarind pea pods to that of a commercial carbon electrode. Two sets of dual-chambered microbial fuel cells have been constructed with carbon electrodes made of industrial carbon and river tamarind pea pods. The two chambers, the anodic chamber, which consists of sludge from Jamboree Lake as a substrate, and the cathodic chamber, which is filled with saltwater solution, were built using two 100-ml plastic containers. An agar-salt bridge connects the chambers. Copper wires attached to a multimeter probe connected the carbon electrodes and were submerged in both chambers. The river tamarind carbon electrode generated a maximum output voltage of 2.75 V, whereas the commercial carbon electrode produced a maximum output voltage of -6.25 V. The output voltage is 9 units higher than a commercial carbon electrode. The use of river tamarind pea pods as a catalyst electrode for microbial fuel cells has been demonstrated to be a cost-effective substitute for the commercially catalyzed electrode used in the oxygen reduction process.